EP705 The uterine mass magna graecia risk index in discriminating between benignant and suspicious malignant uterine masses. (1st November 2019) - Di Cello, A; Borelli, M; Marra, ML; Franzon, M; Visconti, F; Brisinda, C; Di Carlo, C; Venturella, R; Zullo, F
Abstract : Introduction/Background: Recently, we have proposed a prognostic index named Uterine mass Magna Graecia (U.M.G.) as an algebraic formula combining LDH isoenzymes, for discriminating between benignant and suspicious malignant uterine masses. We decided to prospectively evaluate the prognostic value of this score and then evaluate the role of ultrasound (US) imaging in stratifying the risk of sarcoma for women with uterine mass, when it was integrated to the U.M.G. risk index. Methodology: From March 2016 to March 2019 we prospectively enrolled all patients with uterine mass referred at the Unit of Obstetrics & Gynecology of Magna Graecia University of Catanzaro (Italy). In all women we measured lactate dehydrogenase (LDH), LDH isoenzymes and U.M.G. risk index. The vascularization pattern of uterine lesions at the ultrasound (US) was recorded. Quantitative relationships between U.M.G., alone and combined to the US vascularization pattern, and the final diagnosis were investigated. Results: A total of 385 patients with a definitive surgical diagnosis of uterine fibroids and 7 with uterine sarcomas were enrolled. LDH isoenzymes levels significantly differed between patients with benign uterine masses or sarcomas. The accuracy of U.M.G. risk indexin discriminating between benign and suspicious malignant uterine masseswas confirmed with a sensitivity at 100% and specificity at 99.4%, with two false positive over 385 benignant cases and no false negative over 7 sarcomas. The specificity reached 100% when US vascularization pattern was integrated with the U.M.G. score. Conclusion: Based on preliminary data, U.M.G. risk index was confirmed to be as an inexpensive and accurate prognostic index for discriminating between benignant and suspicious malignant uterine masses. The integration of U.M.G. score and US vascularization pattern could improve the specificity into the uterine masses risk stratification. Disclosure: Nothing to disclose.